2014
DOI: 10.1017/jfm.2014.218
|View full text |Cite
|
Sign up to set email alerts
|

Observations of turbulent secondary flows in a rough-wall boundary layer

Abstract: The characteristics of a turbulent boundary layer overlying a complex roughness topography were explored with stereo particle-image velocimetry measurements in the wall-normal-spanwise (y-z) plane. The roughness under consideration was replicated from a turbine blade damaged by deposition of foreign materials containing a broad range of topographical scales arranged in a highly irregular manner. The single-point turbulence statistics displayed strong spanwise heterogeneity, in particular spanwise-alternating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
131
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 21 publications
19
131
2
Order By: Relevance
“…The mean-flow heterogeneity in both cases were here found to be in correspondence of the periodic spanwise roughness spacing. However, although some of the cases herein in examination resemble Barros & Christensen (2014)'s geometry (in particular case LP6), the current investigation found no trace of this heterogeneity in the freestream. This is in disagreement with the aforementioned studies and it is perhaps due to the fact that the spanwise spacing between elements in the cases examined in the current study is not significant enough to induce this characteristic behaviour.…”
Section: Effect Of Surface Morphology On the Roughness Sublayercontrasting
confidence: 72%
See 1 more Smart Citation
“…The mean-flow heterogeneity in both cases were here found to be in correspondence of the periodic spanwise roughness spacing. However, although some of the cases herein in examination resemble Barros & Christensen (2014)'s geometry (in particular case LP6), the current investigation found no trace of this heterogeneity in the freestream. This is in disagreement with the aforementioned studies and it is perhaps due to the fact that the spanwise spacing between elements in the cases examined in the current study is not significant enough to induce this characteristic behaviour.…”
Section: Effect Of Surface Morphology On the Roughness Sublayercontrasting
confidence: 72%
“…This heterogeneity extend outside the RSL all the way to the freestream. This phenomenon is due to the presence of spanwise-wall-normal mean secondary flow in the form of mean streamwise vorticity associated with counter-rotating boundary layer-scale circulations (Barros & Christensen 2014). The latter induces regions of high and low momentum (HMPs and LMPs respectively).…”
Section: Effect Of Surface Morphology On the Roughness Sublayermentioning
confidence: 99%
“…In fact, the layer of gravel was not uniformly glued on the channel bed and, therefore, different topographical scales were arranged in a highly irregular manner. Several studies showed how the formation of these vortical structures are influenced by the roughness height (e.g., [38][39][40]). In general, the identified LMR and HMR patterns tend to occur at spanwise locations of recessed and elevated roughness (relative to the mean elevation), respectively, with the swirling motions residing at spanwise locations of intense spanwise gradients in topographical height [39].…”
Section: Analysis Of the Experimental Datamentioning
confidence: 99%
“…Terrain with heterogeneities along the spanwise direction has been shown to generate secondary flows that manifest as large counter-rotating vortices with axes aligned in the streamwise direction [32,33]. These secondary flows create low-and high-momentum pathways that impact the entire boundary layer thickness and can have serious implications for wind resources as they result in inhomogeneities in the mean wind velocity and turbulence properties.…”
Section: Spanwise Heterogeneity In Surface Terrainmentioning
confidence: 99%